Pemisahan Hukum dan Moral dalam Positivisme Hukum: Implikasi terhadap Penalaran Hakim dan Keadilan Substantif di Indonesia - Rts Fanny Inayah (Universitas Batanghari Jambi, 2026)
This article analyzes the separation between law and morality in legal positivism and its implications for judicial reasoning and substantive justice in Indonesia. The discussion begins from a recurring problem in Indonesian legal practice: legal positivism is often reduced to textual legalism, although positivism as a theory of legal validity is not identical with mechanical adjudication. This study uses normative legal research with conceptual, statutory, and case approaches. The primary legal materials include Law Number 48 of 2009 on Judicial Power, Law Number 1 of 2023 on the Criminal Code, Law Number 1 of 2026 on Criminal Adjustment, and Supreme Court Regulation Number 2 of 2012 on minor crimes and fines. The article finds that positivism contributes to legal certainty because it identifies valid law through authoritative social sources. However, a rigid separation between law and morality may narrow judicial reasoning and produce formally valid but substantively weak decisions. In the Indonesian context, positive law itself provides corrective mechanisms by requiring judges to explore living legal values, prioritize justice when it conflicts with certainty, and consider proportionality in sentencing. Therefore, the problem is not legal positivism as such, but its reduction into narrow legalism. Indonesian law enforcement should combine textual legality with responsible interpretation, proportionality, and the living sense of justice in society.